αConotoxin ArIB[V11L,V16D] is a potent and selective antagonist at rat and human native α7 nicotinic acetylcholine receptors - Innocent, Neal (2008)
A recently developed α-conotoxin, α-CtxArIB[V11L,V16D] is a potent and selective competitive antagonist at rat recombinant α7 nicotinic acetylcholine receptors (nAChRs), making it an attractive probe for this receptor subtype. α7 nAChRs are potential therapeutic targets that are widely expressed in both neuronal and non-neuronal tissues where they are implicated in a variety of functions. Here we evaluate this toxin at rat and human native nAChRs. Functional α7 nAChR responses were evoked by choline plus the allosteric potentiator PNU-120596 in rat PC12 cells and human SHSY5Y cells loaded with calcium indicators. α-CtxArIB[V11L,V16D] specifically inhibited α7 nAChR-mediated increases in Ca(2+) in PC12 cells. Responses to other stimuli (5-iodo-A-85380, nicotine or KCl) that did not activate α7 nAChRs were unaffected. Human α7 nAChRs were also sensitive to α-CtxArIB[V11L,V16D]: ACh-evoked currents in X. laevis oocytes expressing human α7 nAChRs were inhibited by α-CtxArIB[V11L,V16D] (IC(50) 3.4 nM) in a slowly reversible manner, with full recovery taking 15 min. This is consistent with the timecourse of recovery from blockade of rat α7 nAChRs in PC12 cells. α-CtxArIB[V11L,V16D] inhibited human native α7 nAChRs in SHSY5Y cells, activated by either choline or AR-R17779 plus PNU-120596. Rat brain α7 nAChRs contribute to dopamine release from striatal minces: α-CtxArIB[V11L,V16D] (300 nM) selectively inhibited choline-evoked dopamine release without affecting responses evoked by nicotine that activates heteromeric nAChRs. This study establishes that α-CtxArIB[V11L,V16D] selectively inhibits human and rat native α7 nAChRs with comparable potency, making this a potentially useful antagonist for investigating α7 nAChR functions.